STUDI PERANCANGAN SKEMA PULAU BERDASARKAN KOHERENSI GENERATOR PADA SISTEM KELISTRIKAN DKI JAKARTA DAN BANTEN - Hasna Satya Dini; Nanang Hariyanto (Sekolah Tinggi Teknik - PLN, 2018)
This research deals with the islanding scheme design of DKI Jakarta and Banten power system which aim to improve the rate of success in islanding formation when distrubance hit. Islanding scheme is the last option in corrective control that devide electrical system into several regions during disturbance to maintain the electrical system stability. The islanding scheme design method is based on generator coherency, severe connections, and active and reactive power balance. This islanding scheme is designed in 2 steps for 48,3 Hz and 48,1 Hz. In the first step, DKI Jakarta and Banten will be separated from Jawa Bali and in the second step the system should be divided into 4 islands due to generator coherency. Based on simmulation in Digsilent, this islanding scheme design could keep the stability of frequency and rotor angle of DKI Jakarta and Banten system.